Competitiveness and social network of Brazilian fish farmers - Pigatto, Gessuir [UNESP]; Martinelli, Raiane Real; Queiroz, Timoteo Ramos [UNESP]; Bánkuti, Ferenc Istvan (Emerald, 2020)
Purpose: This study aims to present a methodological framework to evaluate the relationship between social network centrality, individual competitiveness and network competitiveness. Design/methodology/approach: Tilapia fish farmers in the Canoas I hydroelectric dam (states of São Paulo and Paraná, Brazil) were provided with a roster of all actors in their network and interviewed to obtain information on relational and competitiveness variables. UCINET was used to calculate the degree centrality of each farmer. Seven competitiveness drivers were combined into a single indicator to determine the level of competitiveness. A four-quadrant matrix was constructed to investigate the relationship between degree centrality and level of competitiveness. Findings: A positive relationship was found between degree centrality and level of competitiveness. Research limitations/implications: Agents upstream or downstream of fish farming were not interviewed, precluding an in-depth analysis of competitiveness in terms of market structure and market relations. The authors suggest that future studies should investigate the influence of upstream and downstream agents on the social network and competitiveness of fish farmers. It is also important to monitor changes in the level of competitiveness of fish farmers in the event of a national economic crisis. Originality/value: Development of a novel methodological framework on the basis of two methodologies, social network analysis and competitiveness analysis.
Keywords: Competitiveness drivers; Degree centrality; Pisciculture; Social network